Child Abuse - (AAP), American Academy of Pediatrics (Pediatric collections., 2019)
Child abuse and maltreatment take many different forms. This collection gives pediatricians and pediatric care-givers the latest findings on diagnosing, treating, and preventing child abuse and the risk factors that often accompany abuse, maltreatment, and neglect.